2013
DOI: 10.1371/journal.pone.0072996
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Distribution and Activity of Prokaryotes in Deep-Sea Surface Sediments of the Mediterranean Sea and the Adjacent Atlantic Ocean

Abstract: The deep-sea represents a substantial portion of the biosphere and has a major influence on carbon cycling and global biogeochemistry. Benthic deep-sea prokaryotes have crucial roles in this ecosystem, with their recycling of organic matter from the photic zone. Despite this, little is known about the large-scale distribution of prokaryotes in the surface deep-sea sediments. To assess the influence of environmental and trophic variables on the large-scale distribution of prokaryotes, we investigated the prokar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 92 publications
3
23
1
Order By: Relevance
“…chemical potential energy) in marine sediments is recognised as another important factor that affects the metabolism, distribution, and dynamics of benthic microorganisms [7, 15, 19]. Specifically, under trophic resource-limiting conditions, heterotrophic Bacteria and Archaea are primarily controlled by BPC and POC-flux [7, 15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…chemical potential energy) in marine sediments is recognised as another important factor that affects the metabolism, distribution, and dynamics of benthic microorganisms [7, 15, 19]. Specifically, under trophic resource-limiting conditions, heterotrophic Bacteria and Archaea are primarily controlled by BPC and POC-flux [7, 15].…”
Section: Discussionmentioning
confidence: 99%
“…9, 13, 19, 31, 33, 44, 57] and a variety of environmental factors have been reported to influence their abundance, such as sediment depth [20], salinity [47], phosphorus [27], organic matter [26], and pH [23]. Only recently, the role of Archaea in biogeochemical processes started to be elucidated, showing that they are involved in organic matter transformation such as methanogenesis [18], anaerobic methane oxidation (AMO, [8]), protein degradation [25], and aerobic ammonium oxidation [22].…”
Section: Introductionmentioning
confidence: 99%
“…The environmental effects were strong in the c-eM basin, where most relationships were context-dependent. Indeed, environmental conditions, such as food depletion or current regime have been reported to be major factors influencing and structuring benthic populations in the Eastern Mediterranean (Tselepides et al, 2000;Króncke et al, 2003;Tecchio et al, 2011;Giovannelli et al, 2013). Furthermore, Zeppilli et al (2016) showed that the high sea floor heterogeneity along an open slope system may shape BEF relationships, even on a very small spatial scale.…”
Section: Bef Relationships On the Basin Spatial Scalementioning
confidence: 99%
“…The deep Mediterranean Sea is a highly oligotrophic environment, where nutrient depletion in surface waters combines with high water temperature, promoting the degradation of sinking organic matter (Sardà et al, 2004). The Mediterranean basin is characterized by a trophic gradient between the less productive eastern basin and the more productive western basin (D'Ortenzio and Ribera d 'Alcalà, 2009;Giovannelli et al, 2013; Table S1), where the greater nutrient inputs are due to river runoff, the inflow of Atlantic surface water, and the outflow of relatively nutrient-rich Levantine Intermediate Water through the Strait of Gibraltar (Bergamasco and Malanotte-Rizzoli, 2010). The Mediterranean open-slope systems selected for the present study are characterized by a high percentage of silt sediment at all depths.…”
Section: Study Area and Sampling Strategymentioning
confidence: 99%
See 1 more Smart Citation